Efficient BiVO(4) Photoanodes by Postsynthetic Treatment: Remarkable Improvements in Photoelectrochemical Performance from Facile Borate Modification - Meng, Qijun (Angew Chem Int Ed Engl, 2019)
Water‐splitting photoanodes based on semiconductor materials typically require a dopant in the structure and co‐catalysts on the surface to overcome the problems of charge recombination and high catalytic barrier. Unlike these conventional strategies, a simple treatment is reported that involves soaking a sample of pristine BiVO(4) in a borate buffer solution. This modifies the catalytic local environment of BiVO(4) by the introduction of a borate moiety at the molecular level. The self‐anchored borate plays the role of a passivator in reducing the surface charge recombination as well as that of a ligand in modifying the catalytic site to facilitate faster water oxidation. The modified BiVO(4) photoanode, without typical doping or catalyst modification, achieved a photocurrent density of 3.5 mA cm(−2) at 1.23 V and a cathodically shifted onset potential of 250 mV. This work provides an extremely simple method to improve the intrinsic photoelectrochemical performance of BiVO(4) photoanodes.